Rain Songs: From Oral Tradition to the Digital Medium (The International Journal of Educational Sciences and Arts, 2026)
The Arab musical heritage is rich and diverse, with songs linked to various contexts such as love, passion, agricultural seasons, cultural specificities, political events, and other themes. Songs celebrating water and rainfall are an essential part of this heritage, as they reflected the Arab people's need for rain during agricultural seasons that required water to ensure crop production and life in general.Celebrating water and rain has been and remains a fundamental part of Arab cultural identity. For example, in the fields of education and upbringing, songs about water contribute to raising environmental awareness among children and teaching them how to conserve and wisely use water. Moreover, technological and media advancements have helped these songs spread through the media and social media platforms, allowing them to persist and influence new generations. Through this research, we will explore how rain songs managed to transition from oral heritage to the modern digital age through media.
Keywords: Rain Song; the Popular Heritage; the Medium